2001
DOI: 10.1080/15604280212527
|View full text |Cite
|
Sign up to set email alerts
|

Markers for Risk of Type 1 Diabetes in Relatives of Alsacian Patients With Type 1 Diabetes

Abstract: Background: The cytotoxic T lymphocyteassociated antigen 4 gene (CTLA-4) encode the T cell receptor involved in the control of T cell proliferation and mediates T cell apoptosis. The receptor protein is a specific T lymphocyte surface antigen that is detected on cells only after antigen presentation. Thus, CTLA-4 is directly involved in both immune and autoimmune responses and may be involved in the pathogenesis of multiple T cell-mediated autoimmune disorders. There is polymorphism at position 49 in exon 1 of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 37 publications
0
4
0
1
Order By: Relevance
“…The T1D risk was not significantly associated with DR4 haplotype and DQB1∗03:02 and DQB1∗06:02 alleles in the present study. In contrast, it was reported in the literature that there were positive associations between T1D and DR4 haplotype [ 8 ] and DQB1∗03:02 allele [ 8 , 28 ]. A protective effect of DQB1∗06:02 allele in T1D was also observed [ 29 ].…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The T1D risk was not significantly associated with DR4 haplotype and DQB1∗03:02 and DQB1∗06:02 alleles in the present study. In contrast, it was reported in the literature that there were positive associations between T1D and DR4 haplotype [ 8 ] and DQB1∗03:02 allele [ 8 , 28 ]. A protective effect of DQB1∗06:02 allele in T1D was also observed [ 29 ].…”
Section: Resultsmentioning
confidence: 95%
“…These results, together, showed that there is a relationship between the presence of these HLA class II alleles, haplotypes, and genotypes and the risk of developing T1D in Beninese as in Caucasoid population [ 8 ]. Indeed, Fajardy et al showed positive associations between DQA1∗05:01 allele and the T1D onset among French children [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…A total of 43 published studies between CTLA-4 and T1D were identified according to our inclusion criteria, involving 8021 cases and 9570 controls (Nistico et al, 1996;Donner et al, 1997;Van der Auwera et al, 1997;Krokowski et al, 1998;Djilali-Saiah et al, 1998;Awata et al, 1998;Yanagawa et al, 1999;Hayashi et al, 1999;Abe et al, 1999;Takara et al, 2000;Lee et al, 2000;Ihara et al, 2001;Kamoun et al, 2001;Osei-Hyiaman et al, 2001;McCormack et al, 2001;Kikuoka et al, 2001;Cosentino et al, 2002;Fajardy et al, 2002;Cinek et al, 2002;Ma et al, 2002;Klitz et al, 2002;Wood et al, 2002;Ongagna et al, 2002;Mochizuki et al, 2003;Bouqbis et al, 2003;Zalloua et al, 2004;Haller et al, 2004;Ide et al, 2004;Ahmedov et al, 2006;Baniasadi et al, 2006;Ikegami et al, 2006;Saleh et al, 2008;Douroudis et al, 2009;Balic et al, 2009;Jung et al, 2009;Korolija et al, 2009;Ferreira et al, 2009;Benmansour el al., 2010;Ei Wafai et al, 2011;Philip and Isabel, 2011;…”
Section: Identification Of Eligible Studiesmentioning
confidence: 99%
“…This substitution leads to the exchange of a threonine to alanine residue [63]. Most casecontrol studies confirm the link between the G allele of this SNP and several AIDs, including T1D in various populations [36][37][38][39]64]. Interestingly, increased proliferation of T cells was found in G/G homozygotes [65,66] but further functional studies are needed.…”
Section: Ctla4mentioning
confidence: 99%